2007
DOI: 10.1111/j.1654-109x.2007.tb00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effectiveness of sowing high and low diversity seed mixtures to enhance plant community development on ex‐arable fields

Abstract: Questions: How is succession on ex‐arable land affected by sowing high and low diversity mixtures of grassland species as compared to natural succession? How long do effects persist? Location: Experimental plots installed in the Czech Republic, The Netherlands, Spain, Sweden and the United Kingdom. Methods: The experiment was established on ex‐arable land, with five blocks, each containing three 10 m × 10 m experimental plots: natural colonization, a low‐ (four species) and high‐diversity (15 species) seed mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 33 publications
4
68
1
2
Order By: Relevance
“…This is not surprising, the small plots of our experiment are bound to be colonized from the surroundings. Although this process is most distinct in studies employing small plots, it has also been observed in in situ restoration experiments using larger plots (Lepš et al ; Baasch et al ). Colonization by natural dispersal is actually regarded as an inherent (and beneficial) property of natural regeneration (Conrad & Tischew ), given sufficient seed sources and connectivity between restoration areas and grasslands in the surrounding landscape (Auestad et al ).…”
Section: Discussionmentioning
confidence: 93%
“…This is not surprising, the small plots of our experiment are bound to be colonized from the surroundings. Although this process is most distinct in studies employing small plots, it has also been observed in in situ restoration experiments using larger plots (Lepš et al ; Baasch et al ). Colonization by natural dispersal is actually regarded as an inherent (and beneficial) property of natural regeneration (Conrad & Tischew ), given sufficient seed sources and connectivity between restoration areas and grasslands in the surrounding landscape (Auestad et al ).…”
Section: Discussionmentioning
confidence: 93%
“…Processes that determine community assembly and finally the composition and number of co‐occurring plant species in a community have been discussed controversially (Chase 2003). Although it has been repeatedly suggested that the close interaction between characteristics of potential invaders and those of the recipient community control the outcome of invasion under similar environmental conditions, different assembly histories due to source‐ or dispersal‐limitation of particular species and different sequences of species arrival at potential sites for invasion may result in a divergent community composition (Fukami et al 2005, Lepš et al 2007). In this experiment we tested the effects of resident species and functional group richness, presence/absence of particular functional groups of resident species and successional age of experimental grasslands on number and identity of species that could invade either spontaneously or after seed addition.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown many times that the initial species richness of newly abandoned field could be very high, but the species richness drops due to spreading of competitively strong species and competitive exclusion of subordinate species (Leps et al, 2007). Although some arable weed species are considered rare and endangered, their survival is usually dependent on regular ploughing and they are not able to survive in permanent grassland, particularly under mesic or wet conditions.…”
Section: Species Richnessmentioning
confidence: 99%
“…This part of the course of the community development is highly idiosyncratic, as it depends on the local conditions and on the presence of a species able under given condition attain high dominance (Leps et al, 2007).…”
Section: Species Richnessmentioning
confidence: 99%
See 1 more Smart Citation